Challenges to the utilization of Community-based Health Planning and Services: the views of stakeholders in Yendi Municipality, Ghana - Bougangue Bassoumah (BMC, 2021)
Abstract Background The Community-based Health Planning and Services (CHPS) is a national health reform programme that provides healthcare at the doorsteps of rural community members, particularly, women and children. It seeks to reduce health inequalities and promote equity of health outcomes. The study explored implementation and utilization challenges of the CHPS programme in the Northern Region of Ghana. Methods This was an observational study that employed qualitative methods to interview key informants covering relevant stakeholders. The study was guided by the systems theory. In all, 30 in-depth interviews were conducted involving 8 community health officers, 8 community volunteers, and 14 women receiving postnatal care in four (4) CHPS zones in the Yendi Municipality. The data were thematically analysed using Atlas.ti.v.7 software and manual coding system. Results The participants reported poor clinical attendance including delays in seeking health care, low antenatal and postnatal care visits. The barriers of the CHPS utilization include lack of transportation, poor road network, cultural beliefs (e.g. taboos of certain foods), proof of women’s faithfulness to their husbands and absence of health workers. Other challenges were poor communication networks during emergencies, and inaccessibility of ambulance service. In seeking health care, insured members of the national health insurance scheme (NHIS) still pay for services that are covered by the NHIS. We found that the CHPS compounds lack the capacity to sterilize some of their equipment, lack of incentives for Community Health Officers and Community Health Volunteers and inadequate infrastructures such as potable water and electricity. The study also observed poor coordination of interventions, inadequate equipment and poor community engagement as setbacks to the progress of the CHPS policy. Conclusions Clinical attendance, timing and number of antenatal and postnatal care visits, remain major concerns for the CHPS programme in the study setting. The CHPS barriers include transportation, poor road network, cost of referrals, cultural beliefs, inadequate equipment, lack of incentives and poor community engagement. There is an urgent need to address these challenges to improve the utilization of CHPS compounds and to contribute to achieving the sustainable development goals.